The Impact of Polyphenols-Based Diet on the Inflammatory Profile in COVID-19 Elderly and Obese Patients - Santos, Juliana Carvalho; Ribeiro, Marcelo Lima; Gambero, Alessandra (Frontiers in Physiology, 2021)
The World Health Organization declared the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2)-associated disease (coronavirus disease 2019 - COVID-19) as a pandemic in March 2020. COVID-19 is characterized by cytokine storm, acute respiratory distress syndrome, and systemic inflammation–related pathology and already kill more than one million of people worldwide. COVID-19 patients with inflammatory comorbidities like obesity and elderly represent a high-risk cluster for rapidly progressive clinical deterioration. These individuals present immunosenescence and comorbid disorders that may promote viral induced cytokine storm and expression of molecules acting as virus receptor as ACE2 and CD26, resulting in respiratory failure and increased morbidity and mortality. A better knowledge of SARS-CoV-2 infection in inflammatory-associated high-risk population is essential in order to develop the therapies needed to combat or prevent severe COVID-19. Here, we review the pathogenesis and clinical implications of inflammatory disorders and disease markers associated to senescence in COVID-19 patients and the emerging evidence to argue that a high intake of polyphenols may have a protective effect on SARS-CoV-2 illness severity.